DNA fingerprinting of human isolates of Burkholderia pseudomallei from different geographical regions of Malaysia - Chua, K.H.; See, K.H.; Thong, Kwai Lin; Puthucheary, S.D. (2010)
Melioidosis is an infectious disease caused by Burkholderia pseudomallei and endemic in Southeast Asia. One hundred and forty six clinical isolates of B. pseudomallei from different states in Malaysia were obtained and molecular typing was carried out using pulsed-field gel electrophoresis (PFGE). Overall, nine clusters were successfully identified. Burkholderia pseudomallei isolates used in this study were found to be genetically diverse and there were differences in the clusters of isolates from peninsular and east Malaysia. BS9 cluster was the most common cluster and found in all the states while BS2 cluster only existed in a particular state. Based on the PFGE analysis, the distribution of different B. pseudomallei clinical isolates in Malaysia was mapped.